The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s10640-020-00411-6
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for $$\hbox {CO}_2$$ Emission Reductions in Passenger Car Transport

Abstract: Passenger car transportation is a major contributor to global carbon emissions. Despite a range of policy measures, the European passenger car fleet remains largely running on fossil fuels. It is questionable whether the lack of emission reductions can be attributed to a lack of consumer preferences for low-emission cars because consumers may have imperfect information about cars' emissions and the availability of clean cars remains limited. This paper investigates the preferences of consumers for emission red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Basic descriptive statistical tools have been used to process the data, namely, growth coefficient, average growth coefficient, relative growth, average relative growth, base coefficient and emissions per capita [23]. To illustrate the indicators clearly, the tables Sustainability 2021, 13, 4771 4 of 20 present even years solely. The growth coefficient k t for individual variables y in time t = 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Basic descriptive statistical tools have been used to process the data, namely, growth coefficient, average growth coefficient, relative growth, average relative growth, base coefficient and emissions per capita [23]. To illustrate the indicators clearly, the tables Sustainability 2021, 13, 4771 4 of 20 present even years solely. The growth coefficient k t for individual variables y in time t = 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Ziegler [11] or Hackbarth and Madlener [12] present additional factors that limit the development of the market with "clean vehicles", such as unavailability of filling stations for alternative fuels, long charging periods for electric vehicles, or a more limited number of models available than is common for conventional automobiles. Hulshof and Mulder [13] state that, firstly, a customer must understand the necessity to implement new measures that result in a decrease in emissions in personal transportation, which will be reflected in their internal willingness to pay. Some authors, for example, Kuwahara et al [14] focus on the development of intelligent transport systems which, thanks to better traffic flow and regulation, will decrease the total emissions.…”
Section: Introductionmentioning
confidence: 99%
“…A range of international studies indicates that people are indeed willing to pay for mitigating carbon emissions. Investigating the WTP for carbon emissions reductions regarding car use, Hulshof and Mulder [16] found that, on average, a Dutch person was willing to pay EUR 199 per tCO 2 emitted in driving (USD ~210/tCO 2 ), when considering what car to buy. MacKerron et al [17] found that the mean WTP for a flight's verified carbon offset among young British adults was GBP 24 per person (USD ~30/tCO 2e ).…”
Section: Selected Studies Of Wtp Of Climate Measuresmentioning
confidence: 99%
“…While degrowth advocates tend to insist that behavioral change, even explicitly betting on a "social miracle" (Kallis 2019, p. 195), is always preferable to any technological risk-taking (Heikkurinen 2018), that overlooks both the scope of the sustainability challenge and the lack of public consent to any sufficiently radical political project (Buch-Hansen 2018). While there may be growing willingness to pay for, say, an electric vehicle (Hulshof and Mulder 2020), giving up private automobile use altogether is obviously a different animal, to say nothing about a more fundamental rematerialization of the economy (Hausknost 2020). Again, the problem is one in which change either (a) remains marginal yet ecologically insufficient or (b) becomes sufficiently radical yet provokes a strong political counterreaction.…”
Section: The Precautionary Principlementioning
confidence: 99%